The impact of women in Congress - Dodson, Debra L.; Oxford eBooks (Oxford : Oxford University Press, 2006)
An assessment of the impact of women members of the US Congress on public policy and Congress itself. Drawing on three key case studies from the 103rd and 104th Congresses, Dodson highlights the complex forces that shape what women members do and their influence on the institution.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States. -- Congress -- 1993-1994); United States. -- Congress -- 1995-1996); Women in politics -- United States; Women legislators -- United States; United States -- Politics and government -- 1993-2001.; Electronic books